Electrochemical sensing and bio-sensing of bisphenol A and detection of its damage to DNA: A comprehensive review - Kambiz Varmira; Milad Saed-Mocheshi; Ali R. Jalalvand (Sensing and Bio-Sensing Research, 2017)
This review is aimed at providing comprehensive information on the applications of electrochemical sensors and biosensors to the determination of bisphenol A (BPA) and detection of its damage to DNA as one of the most important endocrine disrupting chemicals (EDCs). The BPA exhibits endocrine disruption in binding to estrogen receptors, such as alterations in endogenous hormone synthesis, hormone metabolism and hormone concentrations in blood which can cause cancerous tumors, birth defects and other developmental disorders. Therefore, sensitive and selective determination of BPA and its damage to DNA is needed and interesting. Electrochemical sensors and biosensors are very suitable for monitoring because of their excellent selectivity and sensitivity, automation, fast response and good repeatability and reproducibility. In this review, we have provided valuable information about electrochemical sensors and biosensors applied for determination of BPA and detection of its damage to DNA. Keywords: Endocrine disrupting chemicals, Bisphenol A, Electrochemical sensors and biosensors, Electrode modification, DNA damage